2004
DOI: 10.1002/ejoc.200300752
|View full text |Cite
|
Sign up to set email alerts
|

The Convenient Synthesis of Hydrogen‐Bonded Ureidopyrimidinones

Abstract: Blocked isocytosine isocyanates are conveniently obtained by the reaction of 1,1′‐carbonyldiimidazole (CDI) with isocytosines. The resulting precursors for quadruple hydrogen‐bonded structures can be isolated and stored for further use. Reaction with either aliphatic or aromatic amines gives the corresponding mono‐, bi‐, or trifunctional ureidopyrimidinone derivatives in good to excellent isolated yields. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
0
66
0
Order By: Relevance
“…N,NDimethylformamide (DMF) was dried over 4 Å molecular sieves. tert-Butyl 6-hydroxyhexylcarbamate was prepared as reported by Forbes et al 51 Tris[2-(dimethylamino)ethyl]amine (Me 6 TREN) was prepared as reported by Queffelec et al 52 2-(1-Imidazolylcarbonylamino)-6-methyl-4-[1H]-pyrimidinone was prepared as reported by Keizer et al 53 Ethane-1,2-diyl bis(2-bromo-2-methylpropanoate) was synthesized as reported by Matyjaszewski et al 54 n-Butyl acrylate was purified by passing over neutral alumina. Acryloyl chloride was distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…N,NDimethylformamide (DMF) was dried over 4 Å molecular sieves. tert-Butyl 6-hydroxyhexylcarbamate was prepared as reported by Forbes et al 51 Tris[2-(dimethylamino)ethyl]amine (Me 6 TREN) was prepared as reported by Queffelec et al 52 2-(1-Imidazolylcarbonylamino)-6-methyl-4-[1H]-pyrimidinone was prepared as reported by Keizer et al 53 Ethane-1,2-diyl bis(2-bromo-2-methylpropanoate) was synthesized as reported by Matyjaszewski et al 54 n-Butyl acrylate was purified by passing over neutral alumina. Acryloyl chloride was distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…[35][36][37] UPy-based supramolecular polymeric materials prepared from telechelic polymers by functionalization with UPy synthons 18,25,27,38,39 are promising candidates for applications. The rheology of the melt state of such UPy-telechelic polymers is more complex 40,41 than for unidirectionally associated telechelic monomers or for the coordinatively cross-linked polymer networks described by Craig [42][43][44] and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Aer deprotection, an increase in the apparent molecular weight is observed to M n ¼ 18.1 kDa, PDI ¼ 1. 24. The lower molecular weight observed in CHCl 3 compared to THF before deprotection could indicate that P5a has more interactions with the column, which results in an increase in the retention time.…”
mentioning
confidence: 98%